COMPUTATIONAL ANALYSIS OF PHYLOGENETIC RELATIONSHIP OF TAGAP - T CELL ACTIVATION RHO GTPASE ACTIVATING PROTEIN IN SELECTED MAMMALIAN SPECIES - S. H. Abbas; A. Mumtaz; M. J. ul Hasanain; M. E. Babar; M. T. Pervez (Journal of Animal and Plant Sciences, 2021)
The present study was conducted to examine TAGAP gene of selected mammalian species (Cattle, White tufted ear marmoset, Dog, American Beaver, Beluga whale, Horse, Western European Hedgehog, Western lowland Gorilla, Human, Yangtze River Dolphin, Golden Hamster, Mouse, Yangtze finless porpoise, American Mink, Pacific Walrus, Duckbill platypus, Rat, Bolivian Squirrel Monkey, American black bear, Polar Bear and Western Clawed Frog) by evaluating similarity and identity, evolutionary relationship, physicochemical properties, secondary and tertiary structures, and protein-protein interaction. Amino acid and nucleotide sequences were retrieved using UniProt and NCBI. Using MUSCLE integrated in IVisTMSA the MSA (Multiple Sequence Alignment) was produced, while identity and similarity percentage were determined by E-SICT integrated in IVisTMSA. At the end of the experiment, the results showed that there was lowest similarity and identity percentage (40%) among frog and other selected mammalian species. The evolutionary relationship of human and gorilla, mouse and rat evolves from same cluster while all other mammalian species expands cluster according to their related classes. Physicochemical properties of TAGAP protein revealed that Dog TAGAP protein was the least theoretical pI (5.44) while Duckbill Platypus was the highest (8.46) and protein was found to be not only an intra-cytoplasmic protein but also a soluble protein in all selected mammalian species. The secondary structure included the alpha helix, extended strand, and random coil. It can be concluded that TAGAP gene has identical homologue, functional similarity and highly conserved in all selected mammalian species except Western Clawed Frog.
Keywords: TAGAP gene; in-silico analysis; evolution; motifs; STRING; Protein-Protein Interaction (PPI)